Suicide Notes under Judicial Scrutiny in India - Daniela Berti (South Asia Multidisciplinary Academic Journal)
In this paper I focus on particular kinds of texts that may be found in court files on suicides and are commonly known as suicide notes, that is notes supposedly written by a person who has allegedly committed suicide and who wrote down their reason for taking their own life. Unlike most of the “voices” that emerge from a court file, which are always mediated by a legal or judicial representative—the police, the court or the lawyer—suicide notes are not supposed to undergo this legal and linguistic formatting. In fact, unlike other court documents, which in spite of being written in the first person by the witness are an official transcription of an oral statement, the content of a suicide note is supposed to have been originally produced in writing and the person referred to in the note as “I” is supposed to be the author of the note. One of the main issues raised by these notes in court is their authenticity. We are in fact dealing here with texts that appear to have been spontaneously written but whose authenticity is often challenged either by the prosecutor or by the defense lawyer—depending on what is written in the note. The interest these notes have for the anthropologist is therefore twofold. On the one hand, they provide a version of the suicide that is not directly produced by a court officer but is supposedly written by the person who committed suicide or, in the case where it has been fabricated, by the victim’s family or in-laws. On the other hand, these notes are subjected to judicial scrutiny and interpretation; therefore, whether they are real or fictional, they produce a court discourse and they sometimes even appear to have been written with the view to the judicial outcome. I will therefore look at these notes both as a lens which can give access to the deceased’s last thoughts—or to those of her entourage if the note is fabricated—and as a lens used by judges themselves to arrive at a decision